In Vitro Antibacterial Properties of Garlic Extract against Some pathogenic bacteria isolated from burn unit - Azeez , Iqbal; Azeez , Iqbal (University of Thi-Qar Journal of Science, 2019)
The antibacterial effects of aqueous garlic extract and Crude Juice against 38Gram-positive and Gram-negative bacterial isolates, from burn unit were studied. The bacteria isolates were including Staphylococcus spp. , Serratia spp. , Pseudomonas spp., Enterobacter spp., Acinetobacter. Spp. and Ochrobactrum anthropi. were studied. Antibacterial activity of aqueous garlic extract and Crude Juice by cup plate method was characterized by inhibition zones of diameter (14-34) mm for gram-positive bacteria and (14-32) mm for gram-negative bacteria respectively. The results of the study of garlic extract both types of aqueous extract and crude juice in the degree of impact inhibition as results showed that Crude Juice had a greater effect than aqueous extract effect.